GC–MS analysis and in silico approaches to Stichopus hermanii as anti-inflammatory through PKC-β inhibition - Kurnia Fatwati; Asmawati Amin; Lenni Indriani; Rusdina Bte Ladju; Fuad Husain Akbar; Nurlindah Hamrun (Results in Chemistry)
Targeting the NF-κB signaling pathway is an interesting approach for anti-inflammatory therapy. Inhibition of the PKC-β pathway has shown to reducing NF-κB activity. In silico studies using molecular docking techniques used to determine the potentialof Stichopus hermanii as an anti-inflammatory agent are based on PKC-β interactions.The extract was identified via GC–MS to determine the active compound of Stichopus hermanii. The interactions of the active compounds between Stichopus hermanii and the PKC-β receptor were analyzed via PyRx ver.0.8 then visualized via the Biovia v21.1.0.20298 software application. The pharmacokinetic properties were predicted via pkCSM (http://biosig.unimelb.edu.au/pkcsm/). Drug likeness property testing is performed by Lipinski's rule of five http://www.scfbio-iitd.res.in/software/drugdesign/lipinski.jsp. GC–MS analysis revealed the compounds in Stichopus hermanii extract have benefits as anti-inflammatory agents. Analysis of the pharmacokinetic, toxicity and drug-likeness properties revealed that the Stichopus hermanii content has appropriate activity and is nontoxic compared with Ruboxistaurin. Stichopus hermanii have the potential to be candidates for anti- inflammatory drug development through PKC-β inhibition. These compounds with preeminent potential are 1H-Pyrazole, 1,5-dimethyl-; 9-Octadecenoic acid, (E)-; Hexadecanoic acid, methyl ester; 6-Octadecenoic acid and α-Tocopheryl acetate. Through ADMET prediction tests, these compounds exhibited better pharmacokinetics activity and non- toxic.